Evaluación de la calidad de servicio del Centro de Especialidades CONSULMED La Maná, 2023. - Vega Oña, Miguel Angel (2024)
The present project titled “Evaluation of the quality of service of the ConsulMED La Maná Specialty Center, 2023.” The research problem was: What are the determining factors in the quality of service perceived by patients at the ConsulMED La Maná Specialty Center during the year 2023? The general objective was to evaluate the quality of service of the ConsulMED La Maná Specialty Center, 2023. The research that was applied is documentary, field, descriptive and explanatory, using the deductive method and the survey technique, the research instrument was the Questionnaire adapted to the Servqual tool, the population studied was the center's 550 clients, from which a sample of 227 clients was selected. Survey results revealed gaps between customer expectations and perceptions in several categories. In terms of security, there is a small negative gap of [-0.17], indicating that the perceived security is slightly below the expected level. However, the perceived quality slightly exceeds expectations with a positive gap of [0.02]. Customer satisfaction is high, exceeding expectations with a significant positive gap of [0.46]. As for the tangible aspects, there is a negative gap of [-0.28], which suggests that they are not meeting expectations. Finally, empathy significantly exceeds customer expectations with a positive gap of [0.49], this data shows areas where the service meets or exceeds customer expectations and where there are opportunities for improvement. Strategies were proposed based on the findings found in safety and tangibility, to improve the quality of care at the ConsulMED Specialty Center. The beneficiaries of this research will be the clients of the Specialty Center because improvements in the quality of service will increase their satisfaction. It is concluded that clients are dissatisfied in the dimensions of security and tangibility, therefore, these are the aspects in which the establishment must take improvement actions to raise the level of quality of care for its patients. .